A psychometric appraisal of positive psychology outcome measures in use with carers of people living with dementia: a systematic review. (21st April 2021) - Pione, Richard D.; Spector, Aimee; Cartwright, Anna V.; Stoner, Charlotte R.
Abstract: Objectives: This review aimed (i) to identify all positive psychology measures in use with family carers and (ii) to determine their psychometric properties. Design: Literature searches were made in Ovid MEDLINE, PsychINFO, and Web of Science. The identified measures were then subjected to analysis via an established quality appraisal tool. Results: Twenty-five instruments representing the positive psychology constructs of resilience, self-efficacy, and positive aspects to caregiving were found. Two reviewers independently evaluated the measures using the quality appraisal tool. The Gain in Alzheimer Care Instrument, the Resilience Scale, and the Caregiver Efficacy Scale were found to be the highest scoring measures within their respective constructs. Conclusions: Although some robust instruments were identified, there were numerous examples of important psychometric properties not being evidenced in development papers. Future researchers and clinicians should administer evidence-based outcome measures with adequate psychometric properties representing positive and negative constructs to obtain a comprehensive picture of a person's well-being.